Pengaruh Strategi Koping Stres Mahasiswa terhadap Stres Akademik di Era Pandemi Covid-19 - Nadya Nela Rosa; Lina Eka Retnaningsih; Miftahul Jannah (Jurusan Tarbiyah dan Pendidikan, 2021)
This study aims to determine the relationship of coping stress to academic stress during the pandemic covid-19. This research used quantitative methods with the sampling technique used in this research is purposive sampling. The instrument was used a scale of coping stress and academic stress scale distributed using google form media. The data analysis technique used is linear regression analysis. The results of data analysis showed R = 0.235 and a significance level (p) of 0.000 (p <0.01). Based on the results of research and discussion, it can be seen that there is a very significant relationship between coping stress and academic stress.